Forging new paths in the development of community mental health interventions for people with mental illness at risk of criminal legal system contact - Amy Blank Wilson; Natalie Bonfine; Jonathan Phillips; Jamie Swaine; Faith Scanlon; Anna Parisi; Caroline Ginley; Robert Morgan (Health & Justice)
Abstract Background Individuals with serious mental illness (SMI) have disproportionately high rates of criminal legal system involvement. For many, this becomes a repeated cycle of arrest and incarceration. Treatments that address symptoms of mental illness are a critical component of the continuum of services for people with SMI in the legal system; yet on their own, psychiatric treatments have not been successful at reducing criminal legal system involvement for this population. Research suggests that criminogenic risk factors, the major drivers of criminal legal system involvement, are disproportionately prevalent among individuals with SMI. However, promising criminogenic-focused interventions have only just begun to be adapted for individuals with SMI. The proposed study will examine the capacity of Forging New Paths (FNP), a novel criminogenic-focused group intervention developed for individuals with SMI, to engage its primary and secondary outcomes when delivered in community mental health settings. Methods The proposed pilot study will engage a small-scale clinical trial comprising three cycles of FNP delivered in a community mental health center in a Southeastern state in the U.S. The anticipated total sample size is N = 72 and will consist of community-dwelling adults with SMI who have a moderate or higher criminogenic risk level and a history of criminal legal system contact. This study will examine the extent to which FNP is able to engage its primary (aggression and community tenure) and secondary (criminal attitudes and impulsivity) treatment outcomes. Discussion FNP provides an important new service for community-based mental health settings to reduce criminal legal system involvement (and recidivism) among the individuals they serve with SMI. Clinical Trial Registration NCT06290648.